Assessment of radiation Protection in Khuzestan province radiographers - amirhossein davoudian talab; Farshid mahmoudi; mansour barafrashtehpour (Mazandaran University of Medical Sciences, 2015)
Introduction & Purpose: Radiation had been as a continuous and constant hazard in modern medicine which there is no doubt about its harmful effects. The purpose of this study of knowledge, attitude and practice of Radiation worker Khuzestan province towards radiation Protection And provide controlling solutions. Methods: This is a cross-sectional and descriptive analytical study was conducted in Imaging Centers of Khuzestan province in2013. research material contain three questionnaire (Demographic, Knowledge, attitude and practice in radiation protection and open-ended questionnaire), sampling method was Cluster – randomized which After distributing the questionnaires and data collection were analyzed by Using descriptive statistics and Pearson correlation test (SPSS16). Result: Range of age workers was 21-55year with mean 33/92years also. Also not fund a significant relationship Between age, gender, work experience, with knowledge, practice and attitude(P>.05), But between participate in training classes with the knowledge, practice and attitude found positive and significant relationship(p<0.05). Conclusion: Rate of Knowledge and performance the workers Khuzestan province is moderate but is lower than in other studies extraterritorial however the attitude of the workers is desirable. Also the results of this study showed that Target population has Willingness to attend training classes and training and attend training classes can be an effective factor to raise awareness, attitude and practices for radiologists.